Nasal considerations with the Le Fort I osteotomy. (2nd July 2019) - McSwiney, Timothy; Khan, Sadaf; Dhariwal, Daljit
Abstract : Orthognathic surgery involves the correction of severe dentofacial deformities through a combination of orthodontics, surgery and, occasionally, restorative dentistry. This procedure, when involving surgical movement of the maxilla, can lead to changes in the overlying nasal morphology. In this paper, the standard nasal assessment that is undertaken prior to a Le Fort I osteotomy is outlined along with the reported nasal changes seen following this procedure. In addition, the various risk factors associated with adverse nasal changes are considered, as are the management techniques adopted by clinicians to minimize these changes CPD/Clinical Relevance: Clinicians should be aware of the adverse nasal changes associated with the Le Fort I osteotomy.